2021
DOI: 10.1186/s12889-021-11495-0
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder treatment disruptions during the early COVID-19 pandemic and other emergent disasters: a scoping review addressing dual public health emergencies

Abstract: Background During public health emergencies, people with opioid use disorder (PWOUD) may be particularly impacted. Emergent disasters such as the COVID-19 pandemic disrupt already-strained harm reduction efforts and treatment availability. This study aims to answer three research questions. How do public health emergencies impact PWOUD? How can health systems respond to novel public health emergencies to serve PWOUD? How can the results of this scoping review be contextualized to the province o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Regarding the economic impact payments, Tsai et al, (2021) found that those that first received the economic impact payment during the COVID-19 pandemic had a significantly increased use of any illicit drug in the past month. When taken into consideration with the previously identified COVID-19 policy impact on PWOUD such as social isolation, loss of income/ housing, reduced availability of harm reduction strategies and decreased access to MOUD ( Henderson et al, 2021 ), the sudden infusion of economic resources created by the economic impact payments may have also played a contributing role in the exacerbation of the opioid epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the economic impact payments, Tsai et al, (2021) found that those that first received the economic impact payment during the COVID-19 pandemic had a significantly increased use of any illicit drug in the past month. When taken into consideration with the previously identified COVID-19 policy impact on PWOUD such as social isolation, loss of income/ housing, reduced availability of harm reduction strategies and decreased access to MOUD ( Henderson et al, 2021 ), the sudden infusion of economic resources created by the economic impact payments may have also played a contributing role in the exacerbation of the opioid epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…In their review of the treatment disruptions in OUD associated with COVID-19 pandemic measures, Henderson et al, (2021) clearly and succinctly make the case for public policy makers to adequately predict and anticipate the negative consequences of public health measures implemented in future pandemics and not to only focus on one crisis at a time. Del Pozo & Beletsky (2020) suggest that the COVID-19 pandemic has created an opportunity for innovative and adaptive public health and drug policy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations